Notes on Hedyotis L. (Rubiaceae) from Thailand - Wangwasit, Khanit; Chantaranothai, Pranom (Phytotaxa, 2015)
Hedyotis puffii is described and illustrated based on material from Thailand. The new species differs from H. tavoyensis by its obtuse angled stems, usually with (0 ̶ )1 ̶ 2 glands on the calyx margin and the sinus of the calyx that has no interposed subulate teeth. The conservation status of this new taxon is vulnerable (VU D2). In addition the new combination Hedyotis laotica is made and a lectotype is designated.